Reformulating Fraud Crimes Under Article 378 Of The Criminal Code Based On Restorative Justice Values - Rusydianta, Muhammad (Universitas Islam Indonesia, 2021)
Crime of frauds are like an iceberg that always appears till the digital era (such First Travel case). In fact, it is a classic crime since (1915-1918) when ‘the Nederlandsch-Indie Criminal Code’ was enacted. Today, the criminal and penal statutes and their application reflected in Article 378 of the Criminal Code are considered to cause systematic injustice, loss, and suffering, especially for the victims. Then this article needs to be reformulated under the problem formulation